Therapeutic γ-globin inducers reduce transcriptional repression in hemoglobinopathy erythroid progenitors through distinct mechanisms - Dai, Yan (Blood Cells Mol Dis, 2015)
Pharmacologic augmentation of γ-globin expression sufficient to reduce anemia and clinical severity in patients with diverse hemoglobinopathies has been challenging. In studies here, representative molecules from four chemical classes, representing several distinct primary mechanisms of action, were investigated for effects on γ-globin transcriptional repressors, including components of the NuRD complex (LSD1 and HDACs 2-3), and the downstream repressor BCL11A, in erythroid progenitors from hemoglobinopathy patients. Two HDAC inhibitors (MS-275 and SB939), a short-chain fatty acid derivative (sodium dimethylbutyrate [SDMB]), and an agent identified in high-throughput screening, Benserazide, were studied. These therapeutics induced γ globin mRNA in progenitors above same subject controls up to 20-fold, and increased F-reticulocytes up to 20%. Cellular protein levels of BCL11A, LSD-1, and KLF1 were suppressed by the compounds. Chromatin immunoprecipitation assays demonstrated a 3.6-fold reduction in LSD1 and HDAC3 occupancy in the γ-globin gene promoter with Benserazide exposure, 3-fold reduction in LSD-1 and HDAC2 occupancy in the γ-globin gene promoter with SDMB exposure, while markers of gene activation (histone H3K9 acetylation and H3K4 demethylation), were enriched 5.7-fold. These findings identify clinical-stage oral therapeutics which inhibit or displace major co-repressors of γ-globin gene transcription and may suggest a rationale for combination therapy to produce enhanced efficacy.